2018
DOI: 10.1007/s11606-018-4482-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Comparison Feedback on Laboratory Test Ordering for Hospitalized Patients: A Randomized Controlled Trial

Abstract: Clinicaltrials.gov registration: #NCT02330289.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…According to the Institute of Medicine report, variability in the delivery of healthcare is one of the greatest opportunities to improve quality and reduce costs through process improvement and standardisation 44. Similar reduction in variability has been mentioned in prior studies 25 41. Hence, interventions like this help streamline healthcare delivery and reduce variability.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to the Institute of Medicine report, variability in the delivery of healthcare is one of the greatest opportunities to improve quality and reduce costs through process improvement and standardisation 44. Similar reduction in variability has been mentioned in prior studies 25 41. Hence, interventions like this help streamline healthcare delivery and reduce variability.…”
Section: Discussionsupporting
confidence: 75%
“…Studies that used education alone around costs (through fee-display) and indications showed non-significant39 40 reductions, small reductions in utilisation34 or poor sustainability 17. A recent randomised trial that evaluated social comparison alone also did not find a significant reduction in laboratory test utilisation 41. A systematic review of the literature suggests that multicomponent initiatives are more likely to succeed in reducing low-value care 42.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized control trial showed that audit and feedback information had no effect on physician laboratory-ordering practices in the hospital setting. One potential reason for the lack of effectiveness is that physicians did not meaningfully engage with the information -only about two-thirds opened relevant emails and fewer than 20 percent accessed the personalized dashboard during the study (Ryskina et al 2018).…”
Section: The Trade-off Between Effectiveness and Acceptabilitymentioning
confidence: 99%
“…To be effective, all physicians should be obliged to participate in order to include very high-or lowvolume users and ensure accurate representation of the ordering practices of all physicians. To date, personalized audit and feedback has had only modest effect on the total volume of tests ordered, but evidence suggests that it is more effective in reducing practice variation and reducing usage by the most high-volume users (Ryskina et al 2018).…”
Section: Option 1: Physician Education With Mandatory Audit and Feedbmentioning
confidence: 99%
“…5 Ryskina et al attempted to reduce over-ordering of routine lab tests (e.g., CBC, BMP) among hospitalized patients, a ubiquitous problem with significant implications for both hospitalization costs and patients' hospital experiences. 6 This problem is an excellent example of the need to conduct innovative research in how we deliver health care: Over-ordering of routine labs (and the cascade of subsequent work-ups that can follow spurious results) has multimillion-dollar implications for our health system and addressing this problem is one of the Society of Hospital Medicine's five Choosing Wisely campaign recommendations.…”
mentioning
confidence: 99%